English Reading Literacies to Improve Values Among Teenagers - Marudut Bernadtua Simanjuntak; Irma Rasita Gloria Barus (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
People with high levels of literacy usually have low crime rates and high intelligence. It is expected that the school community itself will happen in the school environment like teachers and students. The purpose of this research is to collect information on the learning styles and preferences of young junior high school students who are curious and critical. It is very useful to cultivate interest in reading English literature books in order to increase the cultural and social value of students who intend to apply for school literacy campaigns. The reading literacy development model used is the Plomp model: preliminary research, prototyping and evaluation. Science books such as textbooks recommended by the Cambridge Courses may have a major and popular impact because they can increase their value in various courses that use English. Educators are expected to use related books in their learning and lead the school's reading and writing movement. The result of validation of teaching materials indicates that reading literacy material with the use of English-language publications is important and can be tested.